Functional diversity reveals complex assembly processes on sea‐born volcanic islands. (31st December 2014) - Karadimou, Elpida; Tsiripidis, Ioannis; Kallimanis, Athanasios S.; Raus, Thomas; Dimopoulos, Panagiotis; Prinzing, Andreas
Abstract Questions Do the mechanisms driving community assembly differ between two islands of different age and history of vegetation development? How does sampling scale affect the strength that each assembly mechanism poses on the assembly of plant communities? Location Volcanic islands (Palea Kameni and Nea Kameni) of Santorini Archipelago, Greece. Methods Functional diversity has been proposed as a framework for discriminating among mechanisms of community assembly, such as habitat filtering, limiting similarity and random assembly. We investigated four plant communities in two sea‐born volcanic islands. We recorded plant diversity at scales from 1 m2 to 64 m2. We calculated three indices of functional diversity: functional richness, functional evenness and functional divergence, using 26 functional traits (including vegetative characteristics, ecological preferences and regenerative characteristics). We used null model analysis to test for two different assembly mechanisms: habitat filtering and limiting similarity or random assembly. Results The assemblage of the four communities was complex and did not follow a single mechanism. In most cases, finer‐scale patterns indicated randomness, while coarser scales revealed more structured communities. In the older island, the scrub community was mainly defined by limiting similarity. The therophytic community displayed a limited range of functional traits, indicating mainly habitat filtering, but within this range, the evenness of the distribution indicated limiting similarity. On the younger island, the range of traits did not differ from random. However, within this range of traits, one therophytic community showed signs of limiting similarity, while the second therophytic community displayed uneven functional trait distribution, indicating mainly habitat filtering. The three indices reflected different facets of functional diversity and were not correlated, thus we may argue that they are not redundant, and we even detected different mechanisms of assembly within the same community. Conclusions The functional diversity of the therophytic communities in the younger island implied no specific assembly mechanism; perhaps due to its age, the community is still at the early stages of colonization (i.e. stochastic processes, such as arrival of new species, prevail). In the older island, the lack of disturbances for a long period allowed the establishment of communities assembled by specific mechanisms, such as competition and habitat filtering.